Comparison of female wrestler and female judokas' weight loss situations - Imamoglu, O.; Soygüden, A.; Türkmen, M. (International scientific and professional conference on wrestling: "Applicable research in wrestling", 2017)
AIM: The aim of this research is to compare the women wrestlers and judoist weight loss situations in Turkey. MATERIAL AND METHOD: According to the voluntary principle, 153 women wrestlers and 132 women judoists were filled out the questionnaire developed by the researchers. Statistically t-test and chi-square test were used. RESULTS: The average age of starting to wrestling for women wrestlers was 13.67 years old, and the average age for starting to judo was 11.36 years old. There was no significant difference in age, height and body weight among women wrestlers and judoist (p> 0.05). There was a significant difference between the sport branch starting age and starting age of losing weight (p<.001). In the group of those who continuously lose weight before the competition; 60.08% were in wrestlers, 53.0% in judoist and 57.2% in total in the group. In the group of 36.8% of the athletes declared that they did not lose weight. The athletes of 38.9% who lose weight before the competition were succeeded in the match and 39.9% athletes who didn`t lose weight before the competition were also succeeded in the match. While the rate of those who started to lose weight 9 days or more before the competition was 45.5%, the rate of those who started to lose weight 5-8 days ago was 27.3%. There was no significant difference in the days of starting weight loss before the competition compared to the sport branch (p> .05). CONCLUSION: Similarities and differences were found in weight loss situations for women wrestlers and judoist. Although, the percentage rate of athletes who succeeded in non-weight loss matches was higher, but they lose weight unconsciously. It has come to the conclusion that both athletes in the two branches should be aware of the weight loss.